2010
DOI: 10.1007/s10495-010-0510-z
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PTEN by peroxynitrite contributes to cytokine-induced apoptosis in pancreatic β-cells

Abstract: Phosphatase and tensin homolog (PTEN), a tumor suppressor gene, by negatively regulating the PI3K-Akt signaling pathway, participates in multiple biological processes such as cell proliferation, apoptosis, differentiation, and migration. Recent studies show that selective deletion of PTEN in pancreatic beta-cells leads to resistance to streptozotocin (STZ)-induced diabetes, but the mechanism is unclear. One major mechanism underlying STZ toxicity is cytokine-mediated beta-cell destruction in which oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
1
10
1
Order By: Relevance
“…The oxidative stress pathway genes regulated by IL-22 have the capability to decrease intracellular concentrations of O 2 − , H 2 O 2 , NO, OH and ONOO − , plausibly explaining how IL-22 prevents ER stress. Downregulation of iNOS will limit production of NO, a mediator of the beta cell response to cytokines, NEFAs and high glucose and a trigger for apoptosis 10 40 and beta cell apoptosis 41 . Prdx5 highly efficiently reduces peroxynitrite 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative stress pathway genes regulated by IL-22 have the capability to decrease intracellular concentrations of O 2 − , H 2 O 2 , NO, OH and ONOO − , plausibly explaining how IL-22 prevents ER stress. Downregulation of iNOS will limit production of NO, a mediator of the beta cell response to cytokines, NEFAs and high glucose and a trigger for apoptosis 10 40 and beta cell apoptosis 41 . Prdx5 highly efficiently reduces peroxynitrite 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relative concentrations of LPS and metformin in different experimental conditions may determine the final effect of metformin on inflammation. In addition to their interaction in inflammatory signaling, a previous report has shown that LPS upregulates PTEN expression [31] , and PTEN is important for the negative regulation of PI3K activity, an upstream signaling component of PKB [32,33] . We assessed PTEN abundance and found that LPS clearly increased its expression in both skeletal muscle and the liver, while metformin reduced its expression.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN was initially identified as a tumor suppressor, and its loss or mutation is reported to be associated with the development of various cancers (16,17). PTEN may exert this regulatory role by altering its own expression and activity in response to external stimuli such as inflammatory mediators or cytokines (18,19). In addition, some studies have revealed decreases in PTEN expression by TNF (20) or cigarette smoking (21).…”
mentioning
confidence: 99%